The Personal Bibliography of Jonas Basanavičius as a Source for Biographical Studies - Miknienė, Giedrė (Bibliotheca Lituana, 2019)
The article presents a bibliographic index compiled in the Wro- blewski Library of the Academy of Science and discusses the significance of a personal bibliography for biographical studies. This is the first and so far the only comprehensive index encompassing both Basanavičius’s own publications and writings about him. The first part of the index, dealing with writings by Basanavičius, was published in 2015. The second part, concerning literature on him, is currently under preparation.Both biographical studies and research in other scientific fields will benefit from the following aspects of the bibliography: it offers clarification on Ba- sanavičius’s pseudonyms and contains entries for his anonymously published works, documents signed by him, and repeated editions of his writings. It also provides citation data, i.e., information on who cited Basanavičius’s works or commented on them.The bibliography will be useful in studying Basanavičius’s biography, the subject variety in his writings, their dissemination and popularity, as well as the historical circumstances in that time period. The bibliography also will be of use in writing a scientific biography of Basanavičius or a monograph about him, as well as in preparing a comprehensive edition of his writings.Based on the example of the bibliography of Basanavičius, it may be stated that a personal bibliography is an important source for biographical studies, which may be instrumental in creating a comprehensive biographical portrait of an individual.
Keywords: biographic research; personal bibliographies; information sources; Jonas Basanavičius; bibliographic databases